Data to the knowledge of the fauna of plume moths (Lepidoptera: Pterophoridae) of Georgia - P.Ya. Ustjuzhanin; V.N. Kovtunovich; L. Matuszewski (Кавказский энтомологический бюллетень, 2025)
An annotated list of species of Pterophoridae (Lepidoptera) from Georgia is compiled based on our material and literature data. Te material was collected in 11 localities in 2022–2024. To date, 45 species of Pterophoridae are known from Georgia, 13 of which are recorded for the frst time for the fauna of the country